The Influence of Social Media, Price, and Servicescape on Purchasing Decisions at Warkop Mie Aceh Hijrah Jaya in Medan Amplas - Syafrin Ananda Harahap; Rukmini Rukmini; Muhammad Hilman Fikri; Wan Dian Safina; Toni Hidayat; Muhammad Rizaldy Wibowo (International Forum of Researchers and Lecturers, 2025)
This research aims to determine the influence of Social Media, Price, and Servicescape on Purchase Decisions at Warkop Mie Aceh Hijrah Jaya Medan Amplas. In this research, data collection was conducted using purposive sampling, with a sample of 84 respondents. All analyses in this research were assisted by the SPSS 25.0 software. The data analysis techniques used included classical assumption tests, multiple linear regression analysis, and hypothesis testing. Based on the t-test results, it was found that the significance value (Sig.) of Social Media was 0.000 < 0.05 and the t-count value (3.783) > t-table (1.664). Therefore, it can be concluded that the Social Media variable has a positive and significant influence on the Purchase Decision variable. Furthermore, the significance value for the Price variable was 0.000 < 0.05, and the t-count value (5.435) > t-table (1.664). Thus, it can be concluded that the Price variable significantly influences the Purchase Decision variable. Next, the significance value for the Servicescape variable was 0.000 < 0.05, indicating a significant influence on the Purchase Decision variable. Based on the data, the t-count value was (9.892) > t-table (1.664). Therefore, it can be stated that the Servicescape variable has a positive and significant influence on the Purchase Decision variable.